Tax law (Scandinavian Studies in Law) (Stockholm Institute for Scandinavian Law, 2003)
This volume of Scandinavian Studies in Law is devoted to legal problems relating to taxation. The book comprises twenty-four articles covering many different areas of national and international taxation. The contributions are all written by scholars in the Scandinavian countries Denmark, Finland, Norway & Sweden. The Scandinavian countries all have comprehensive social welfare systems and huge public sectors - this has resulted in high standards for social security, but also in some of the world's highest taxes. As a consequence, Scandinavian tax laws are frequently debated in the political arena